Effects of cultivar and planting period on growth, yield, macilage and nutritional composition of corchorus olitorius under field and shade house conditions - Mothoa, Pabalelo Emmanuel (My University, 2022)
The awareness of the nutritional benefit and consumption of the Jew’s mallow (Corchorus olitorius L.) especially in South Africa is low; this is predominantly because of lack of access and availability of the crop in the market. This research aimed to determine to what extent would the planting period affect mucilage, growth, yield and nutritional composition of the selected C. olitorius cultivar under different growing conditions and provide a better understanding and scientific evidence for the producers to maximize production. The experiments were carried out simultaneously, the first experiment (field trial), was on the field and the second (pot trial) in the shade house. Treatment factors were: 2 x growing conditions (field and pot), 4 x planting periods (November, December, January and February) and 3 x C. olitorius cultivars (‘Local’, ‘Oniyaya’ and ‘Amugbadu’). The experiments were carried out as randomised complete block design (RCBD) arranged in split-spilt plot with three replications. Growing condition was the main factor, planting period as the sub-factor, while the cultivars were the sub-subplot factor. Mucilage content, growth and yield parameters were measured and nutritional composition of the crop was determined from harvested plant samples. Mucilage content of C. olitorius varied with cultivar and growing condition. The significantly (P < 0.05) highest quantity of mucilage at 8 WAT was obtained from Oniyaya cultivar under field condition whereas the least was recorded from Local cultivar under pot condition. The mucilage content of the three cultivars did not differ significantly (P ≤ 0.05) at 6 WAT, however significant (P < 0.01) differences were recorded at 8 WAT. The cultivar Oniyaya produced significantly highest average (184.58 mPa.s) mucilage content at 8 WAT while the lowest average value (124.58 mPa.s) was recorded in the Local cultivar. This implies that Oniyaya cultivar produced the slimiest plants. The mucilage content of Jew’s mallow appears to decline over time; thus, the crop had higher mucilage content when young and tender. Selected growth parameters such as chlorophyll, number of leaves and stem diameter were significantly affected by the combined effect of cultivar, planting period and growing condition. For example, the average highest chlorophyll content was obtained in Oniyaya cultivar during November period under pot conditions. While the greatest number of leaves at 8 WAT were obtained in Oniyaya and Local cultivars during xxvii December planting period and in Amugbadu during November period all under the field conditions. All cultivars grown during the February planting period had the lowest average number of leaves. Growth parameters such as number of branches, plant height and leaf area were not significantly (P ≤ 0.05) affected by the combined effect of cultivar, planting period and growing condition. Significant (P < 0.05) combined effect of cultivar and planting period was recorded on number of C. olitorius branches at 6 WAT. Furthermore, significant interaction between planting period and growing condition was also recorded. The significantly higher number of branches at 6 WAT was obtained from Oniyaya and Amugbadu cultivars during the November planting period. The test crop seedlings transplanted in February had the lowest average number of branches. Comparing the cultivars at 6 and 8 WAT, Oniyaya produced significantly (P < 0.01) higher number of branches than Local. Local cultivar was significantly taller than others under the field condition; while significantly tallest plant was obtained during December period under the same condition. The differences observed in C. olitorius shoot and root fresh and dry masses were not significantly different in their responses in relation to the combined effect of cultivar, planting period and growing condition. However, the significantly highest average fresh shoot mass was obtained during December period and the lowest average values in February planting period. The combined effect of cultivar, planting date and growing condition had significant (P < 0.01) influence on number of days to 50% flowering; pod formation and pod maturity of C. olitorius. The significantly longest average number of days to 50% flowering was observed in Oniyaya and Amugbadu cultivars during November period under field condition, while Local cultivar flowered at the shortest period, but produced highest number of pods and seed yield during the December planting period under the same condition. Cultivar, planting date and growing condition had significant (P < 0.01) influence on Zinc contents of C. olitorius. Whereas the three factors had no significant effect on N, Ca, Mg, K, Na, Mn, Fe, P, Al, ash and dry matter contents of the crop. The highest average amounts of N, Mg and K were obtained from Local cultivar during November period while the same cultivar produced the highest average amount of Ca during December period. In conclusion, the mucilage content and fresh shoot mass (which is xxviii the marketable part of C. olitorius) were optimal in crops grown during the December planting period when the temperatures are at the highest. While better nutritional content of the crop was better attained during the November planting period. Both November and December planting periods allowed C. olitorius to reach its maximum growth capacity, translating to higher yielding parameters than other planting periods.
Thesis (M.Sc. (Horticulture)) -- University of Limpopo, 2022
Keywords: Cultivar; Planting period; Growing condition; Mucilage; Corchorus olitorius; Malvaceae; Tossa jute; Mucilage